PROPHETIC COMMUNICATION AS A JUDGE ANALYSIS OF COMMUNICATION IN HADITH ABOUT LIES IN TESTIMONY - Fitah Jamaludin (Indonesian Journal of Islamic Communication, 2024)
Communication is a term that describes one of the types of human relationships used to share ideas and concepts between two or more parties. For the communication process to be executed, a minimum of two parties is required, as an individual cannot communicate solely with themselves. The communication process also involves sharing ideas, symbols, words, images, and numerous other messages that convey specific meanings. Communication is an essential part of our daily activities, and no individual can live without it. Socialization, education, and learning are heavily dependent on communication. The more positive and skilled the communication, the greater the value and superiority of what we learn. Especially when the communicator holds authority in making decisions. In the story of a hadith, Prophet Muhammad SAW taught the method of communication to false witnesses, demonstrating wise communication while also issuing a warning. Based on these issues, this research formulates two main problems: 1) How did the Prophet Muhammad SAW communicate? 2) How did the Prophet analyze the method of communication with false witnesses? This research uses a qualitative method with a sociological theory approach. The conclusion of this research shows how the Prophet provided advice. In the communication conducted, the Prophet emphasized the importance of speaking good words, being truthful, giving advice with kindness, and issuing a warning to false witnesses.